PENGARUH PEMBERIAN SUPLEMEN BESI SAAT MENSTRUASI TERHADAP PENINGKATAN KADAR HAEMOGLOBIN PADA REMAJA DI SMUN I BANTUL YOGYAKARTA - Puspitasari, Dian; Ardiana Sari, Alfie (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Female teenagers is vulnerable group to suffer from anemia. Anemia in teenagers is mainly caused by poor quality of dietary habits. It will lead to delayed growth and development and lower school performance due to fatigue, loss of passion, and concentration difficulty. Female teenagers require iron to be stored as they are expectant mothers who will give birth in the future. Anemia will put then at a high risk for having babies with low birth weight (LBW). Objective: This research aimed to measure the increased level of hemoglobin after iron suplementation during menstruation in female teenagers. Method: Research was a quasi-experiment with two groups. Control and treatment group, each consisted of 16 female teenagers at SMAN I Bantul Yogyakarta. Result: Hemoglobin level in the treatment group increased significantly after suplementation. Whereas, the control group did not show difference after suplementation. Conclusion: Iron supplementation during menstruation and once every week can increase hemoglobin level in teenagers at SMAN 1 Bantul Yogyakarta. Keywords: Hemoglobin, Anemia, Female Teenager